The current state of the complex socioeconomic development of rural areas (Вестник КазНУ. Серия Экономическая, 2016)
Currently, the problem of rural development attracts the attention of re- searchers for the development of the local economy and local governance. The development of local self-government requires the decentralization of power, that is, the transfer of rights under the order of the resources gov- ernments in rural areas, the real participation of the population in the ad- ministration of the territories. A prerequisite for the social development of rural areas, as the Kazakh and foreign practice, is the level of development of local government. However, these factors are closely linked: the devel- opment of local self-government contributes to the rise of the agricultural sector; in turn, improve the financial condition of the industry creates the preconditions for the development of social infrastructure of the village. The development of local self-government talks about the importance and depth of the process - changing ideological foundations of society, shap- ing it into a relationship based on more equitable principles that provide a high social and economic impact. Consequently, the role of local govern- ment in social and economic development of the village is extremely high